How Does the Use of Accounting Information Systems and Internal Control Affect Employee Performance? A Moderation Analysis of Work Motivation - Aldona, Iqlima Febriyanti; Almaidah, Siti (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study investigates how accounting information systems (AIS) and internal control systems affect employee performance. Work motivation is used as a moderating variable. Accounting information systems are very important for companies, especially in the era of globalization and increasingly rapid technology. In the era of globalization and rapid technological development, companies including Savings and Loan Cooperatives in Surakarta face challenges in improving employee performance in order to remain competitive. For this reason, an effective and efficient accounting information system (AIS) and a strong internal control system are needed, because both are believed to help in decision making, supervision, and work planning. However, the effectiveness of these two systems in improving employee performance cannot be separated from the work motivation possessed by individuals. In other words, the level of work motivation is an important key in strengthening the influence of AIS and internal control on employee performance. Information such as orders, sales, and payments are recorded in this system, which is needed by managers and employees for control and planning. Good performance can be seen from an increase in employee quality and productivity, and a decrease in absenteeism. A good accounting information system helps decision-making and satisfies users. Quality internal controls increase productivity and protect company assets. Employee motivation also affects performance, and perceived needs are important for motivation. This research focused on Surakarta City Savings and Loan Cooperative. Quantitative methods were used to collect primary data from a survey conducted on 100 employees working in various positions in the company. The results showed that the desire to work increases according to the two independent variables and employee performance, or the process the greater the work motivation, the greater the performance of workers affected by internal control and AIS. This research shows that a strict internal control system and proper use of accounting information technology are essential to increase employee productivity.